Upaya Guru Dalam Mengembangkan Kreativitas Anak Usia Dini di Kota Pontianak - Miranda, Dian (Jurnal Pembelajaran Prospektif, 2016)
It is time to consider aspects of creative education in educating the students, especially in the era of globalization which is full of competition.Creativity is needed in terms of making something new. This study aimed to look at the efforts of early childhood teachers in developing the creativity of early childhood teachers at ten-early childhood institutions (PAUD) in the city of Pontianak in 2015. The method used in this research was by direct observation using a structured observation instruments. The results obtained, by the 80% of teachers observed had to do things that support the creativity of the PAUD with excellent category, but 50% of the teachers still did inhibit creativities.